2017
DOI: 10.18203/2394-6040.ijcmph20174849
|View full text |Cite
|
Sign up to set email alerts
|

Water sanitation and hygiene in the schools of rural field practice area of Shri B. M. Patil Medical College, Vijayapur

Abstract: Background: One of the world's most urgent issues is lack of safe water, sanitation and hygiene. Water-related improvements are crucial to meet the development goals, reduce child mortality, and improve health in a sustainable way. The absence of WASH in schools is responsible for 20% of total deaths and disability adjusted life years (DALYs) in children. Over 440 million schools days are missed annually due to water, sanitation and hygiene related diseases. Though there are emerging vaccines for rotavirus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
3
0
0
Order By: Relevance
“…About 48.67% of schools were having improved toilets which are single-sex which were also less as compared to other studies. [ 12 13 ] Our study revealed that less percentage of schools were having hand-washing facilities with less number of schools were having both soap and water which was also observed in other studies. [ 11 13 14 15 16 ]…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…About 48.67% of schools were having improved toilets which are single-sex which were also less as compared to other studies. [ 12 13 ] Our study revealed that less percentage of schools were having hand-washing facilities with less number of schools were having both soap and water which was also observed in other studies. [ 11 13 14 15 16 ]…”
Section: Discussionsupporting
confidence: 84%
“…[ 12 13 ] Our study revealed that less percentage of schools were having hand-washing facilities with less number of schools were having both soap and water which was also observed in other studies. [ 11 13 14 15 16 ]…”
Section: Discussionsupporting
confidence: 82%
“…Though washing facility was adequate, availability of soap was not as per Swachh Bharat Swachh Vidyalaya guidelines which require all schools should provide soap for hand washing. In a study done by Hullalli et al, 7 in schools of Karnataka, all the had hand washing facilities which is similar to the present study but availability of soap was less (42.8%) than the present study. In another study by Tamilarasi et al, 8 64.7% participants had separate hand washing stations and 65.3% participants reported continuous supply of water which is less than present study and reason may be because this study was done when Swachh Vidyalaya program had just started.…”
Section: Discussionsupporting
confidence: 83%